The long noncoding RNA noncoding RNA activated by DNA damage (NORAD)-microRNA-496-Interleukin-33 axis affects carcinoma-associated fibroblasts-mediated gastric cancer development. Issue 2 (20th December 2021) - Huang, Chaoqun; Liu, Jiuyang; He, Liang; Wang, Fubing; Xiong, Bin; Li, Yan; Yang, Xiaojun
ABSTRACT: Carcinoma-associated fibroblasts (CAFs) are one of the crucial parts of in the tumor microenvironment and contribute to tumor progression. Interleukin-33 (IL-33), a tissue-derived nuclear cytokine from the IL-1 family, has been found abnormally expressed in tumor cells and Fibroblast. However, the role and mechanism of IL-33 in the interaction between gastric cancer (GC) cells and CAFs need investigation. Presently, we inquire into the function of lncRNA NORAD-miR-496 axis-mediated IL-33 in modulating the GC-CAFs interaction. Real-time reverse transcription-polymerase chain reaction (RT-PCR) was adopted to gauge the expression of NORAD, miR-496, and IL-33 in GC tissues and cells, and gain- or loss-of-function assays were conducted to investigate the role of them in GC. A GC cell-CAFs co-culture model was established to explore the interaction between CAFs and GCs. As exhibited, NORAD was up-regulated in GC tissues and cells, while miR-496 was remarkably down-regulated. Overexpressing NORAD substantially promoted the proliferation, migration, invasion, and EMT of GC cells and repressed cell death, while overexpressing miR-496 had the opposite effects. Additionally, NORAD enhanced the IL-33 expression and the release of IL-33 from GC cells. The dual-luciferase reporter assay confirmed that miR-496 was a target of NORAD and targeted IL-33. CAFs aggravated the malignant behaviors of GC cells as indicated by both experiments. However, NORAD knockdown in CAFs reversed CAFs-mediated promotive effects on GC cells. In conclusion, NORAD enhanced the promotive effect of CAFs in GC cells by up-regulating IL-33 and targeting miR-496, which provided new insights into the microenvironment of GC cells and CAFs. Abbreviation ANOVA: Analysis of Variance; BCA:Bicinchoninic acid; CAFs: carcinoma-associated fibroblasts; CCK-8: cell counting kit-8; ceRNA: competing endogenous RNA; DAPI: 4′, 6-diamidino-2-phenylindole; DMEM: Dulbecco's minimal essential medium/Ham's; ECL: enhanced chemiluminiscent; ELISA: Enzyme-Linked Immunosorbent Assay; EMT: epithelial-mesenchymal transition; FBS: fetal bovine serum; FISH:Fluorescence in situ hybridization; FITC:fluorescein isothiocyanate; FSP:fibroblast-specific protein; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GC: gastric cancer; IHC: immunohistochemistry; IL: Interleukin; lncRNA: long Noncoding RNA; miR-496: microRNA-496; MMP-14:matrix metalloproteinase-14; MUT:mutant; MYH9: myosin heavy chain 9; NFs: normal fibroblasts; NORAD: Noncoding RNA activated by DNA damage; ORF: open reading frame; PBS: phosphate-buffered saline; PMSF: Phenylmethylsulfonyl fluoride; PVDF: polyvinylidene difluoride; RIPA: Radio-Immunoprecipitation Assay; RT-PCR: Real-time reverse transcription polymerase chain reaction; S100A4:S100 calcium binding protein A4; SDS-PAGE: sodium dodecyl sulfate-polyacrylamide gel electrophoresis; sh-NC: short-hairpin RNA negative control; sh-NORAD: short-hairpin RNA of NORAD; α-SMA: α-smooth muscle actin; TBST: Tris-buffered saline with Tween-20; TGF-β1: Transforming growth factor β1; TUNEL: TdT-mediated dUTP Nick-End Labeling; TWIST1: the twist-related protein 1; VEGF-C: vascular endothelial growth factor C; WT: Wildtype.